Sixteen Inuit on board whaling schooner, west coast of Hudson Bay, Canada - Comer, George (Creator); American Museum of Natural History (Creator) (Ownership Statement: Mystic Seaport, 1897)
A group of sixteen Inuit pose on board a whaling schooner, identified as the Era or A.T. Gifford, on the west coast of Hudson Bay, Canada. The group appears to include children as well as men. Lifestyle Livelihood Infrastructure Title supplied by cataloger. The schooner Era was built in 1847 at Boston, Massachusetts. She was a New London whaling vessel until her last voyage out of that port in 1892; her masters included James Monroe Buddington, John O. Spicer, and George Comer. She was wrecked off Miquelon Island, July 27, 1906. The schooner A.T. Gifford was built in 1883 at Essex, Massachusetts. George Comer was her master during one of his Arctic voyages in which he mapped areas in the Hudson Bay area. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment. Slide prepared by the American Museum of Natural History, New York, from an original photograph by Captain George Comer. Slide was used by Comer to illustrate lectures about his Arctic and seafaring experiences.